A Reliable Nano Device with Appropriate Performance in High Temperatures. (28th February 2017) - Zareiee, Meysam; Mehrad, Mahsa
Abstract : There are many problems during designing MOSFETs in nano scale regime. Some problems contain high gate current, high off current and high electron temperature. These problems are created when the peak of electric field is high which causes reducing the device reliability. So, reducing the peak of electric field can be an objective during designing a device. In this paper, a new structure for improvement of the partial SOI MOSFET parameters is presented. So, oxide layers are considered in the channel and in the extended drain region to reduce the peak of electric field. This reduction results in achieving reduced off current, gate current and electron temperature. The simulation with ATLAS simulator shows that the new structure has improved hot carrier effect and its reliability is more than conventional one.